Correlation between social factors and anxiety-depression in function dyspepsia: do relationships exist? - Huang, Zhen-Peng; Yang, Xian-Fen; Lan, Li-Sa; Liu, Tao; Liu, Cheng-Li; Li, Jin-Li; Liang, Zhong-Hui (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction: Function dyspepsia (FD) may cause patients to suffer from anxiety and depression, and psychosocial disorders would have a significant effect on FD symptoms. Aim : To examine the prevalence of anxiety and depression among function dyspepsia (FD) patients and to identify social factors of anxiety-depression among FD patients. Material and methods : Patients with FD, who fulfilled the Rome III criteria, were enrolled. All patients were administered a validated Chinese version of the self-rating scale (SDS) and self-rating anxiety scale (SAS), and investigated regarding the patients’ social factors. Results: A total of 907 patients were enrolled, including 516 (56.89%) FD patients within anxiety-depression status; SDS mean scores were 51.57 ±8.22; SAS mean scores were 51.04 ±7.53; 52.28% were male and 64.25% were female (χ 2 = 262.54, p < 0.01); 56.16% were aged 18–29 years, 54.15% were aged 30–39 years, 54.77% were aged 40–49 years, 62.02% were aged 50–59 years, 69.23% were aged above 60 years (χ 2 = 18.14, p < 0.01); 67.44% were the retirees; 63.31% were manual workers; 55.10% were soldiers; 43.57% were mental workers; 38.89% were students (χ 2 = 716.53, p < 0.01); 64.20% had junior high school degree or below; 57.36% had high school degrees; 42.03% had college degrees; 44.44% had master’s or above degrees (χ 2 = 27.21, p < 0.05); 38.10% were in good health condition; 61.90% were in poor health condition (χ 2 = 7.94, p < 0.01); 20.31% had correlative family history; and 79.69% had no correlative family history (χ 2 = 2.23, p > 0.05). Conclusions : The FD patients have higher rates of anxiety and depression. Gender, age, occupation, education level, and health condition have a significant effect on anxiety and depression status. Female gender, advanced age, high-stress occupation, lower education level, and poor health condition all are risk factors. Family history has no relationship with anxiety and depression among FD patients.